High frequency vibration analysis in drilling of GFRP laminates using candlestick drills. (15th January 2018) - Liu, Liping; Wu, Feng; Qi, Chunliang; Liu, Tianshu; Tian, Jing
Abstract: The vibration signal contains a lot of information closely related to the tool performance in drilling the composite material. However, due to the limit of the frequency response characteristics of piezoelectric accelerometer, the monitored vibration signals used in researches were usually below 10 kHz. Thus, the high frequency vibration signal was ignored. Drilling experiments of Glass Fiber Reinforced Plastic (GFRP) laminates were carried out utilizing candlestick drills in this article. The high frequency vibration signals of ten candlestick drills with different drill tip geometry parameters were analyzed and compared in time domain, frequency domain and in bispectrum. The results revealed that there was high frequency vibration signal above 10 kHz in the process of drilling GFRP laminate. These signals were sensitive to the changes of the drill tip geometry parameters. The changes of the bispectrum energies of these signals could reflect the changes of the cutting performances and the delamination factors for the drills.